United Nation Security Council Legal Politics Against Countries Violating International Humanitarian Law - Syah, Nurijlal Hafizh; Sudiro, Ahmad (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The United Nations Security Council is a forum created by the United Nations based on the United Nations Charter which contains good and noble goals for the creation of peace and harmony among countries in the international region. The United Nations Security Council with all the specificities given by the United Nations makes this association an international law enforcer for countries that violate international customs and norms. However, not in line with the purpose and function of the establishment of the United Nations Security Council, often the Security Council shows a political-legal attitude that is contrary to its duties and functions, the use of veto privileges that should be used for countries that violate the provisions of international humanitarian law is instead used to exert political emphasis in order to achieve a global domination. Then the question is about the practice of legal provisions applied by  the United Nation Security Council in imposing international sanctions against countries in conflict and the legal responsibility of the UN Security Council against countries that violate the provisions of humanitarian law in armed conflicts. This study aims to find out and observe the provisions of international law applied by  the United Nation Security Council (UNSC) in imposing international sanctions against countries in conflict, as well as to know, study and analyze the responsibility of the UN Security Council in imposing sanctions against countries that violate the provisions of humanitarian law in armed conflicts. Furthermore, this study uses a normative research method with Primary Legal Materials in the form of expert interviews and secondary legal materials in the form of international legal agreements and international regulations. That in terms of practice, the UN Security Council needs to carry out its duties and functions in accordance with the regulations stipulated in the UN Charter and prioritize the principles that are upheld in the midst of the United Nations by always adhering to its legal responsibilities.